2021
DOI: 10.1111/bjc.12276
|View full text |Cite
|
Sign up to set email alerts
|

The effect of medication and question wording on self‐reported symptoms and their accuracy in young adults with attention‐deficit/hyperactivity disorder

Abstract: Objectives. This study examined the effect of whether participants were on or off their medications and the effect of questionnaire wording on self-reported symptoms in young adults with ADHD. Additionally, this research evaluated the relationships between these self-reported symptoms and objective performance on measures of working memory.Design. This experimental study utilized a mixed factorial design with one betweensubjects factor (whether participants were unmedicated or medicated at the time they comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The researchers found that the subjects whom were asked about their habits were significantly more likely to donate blood than their control counter parts at the following blood-drive (Godin, Sheeran, Conner, & Germain, 2008). Other researchers found that when clinicians did not ask patients with Attention Deficit Hyperactivity Disorder (ADHD) to report whether they were currently medicated on a disease-related severity questionnaire, patients were more likely to report un-medicated symptomologies (Lineweaver et al, 2021). In other words, patients on ADHD medications responded more symptomatically similar to their un-medicated selves when their medication status was not included on the questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…The researchers found that the subjects whom were asked about their habits were significantly more likely to donate blood than their control counter parts at the following blood-drive (Godin, Sheeran, Conner, & Germain, 2008). Other researchers found that when clinicians did not ask patients with Attention Deficit Hyperactivity Disorder (ADHD) to report whether they were currently medicated on a disease-related severity questionnaire, patients were more likely to report un-medicated symptomologies (Lineweaver et al, 2021). In other words, patients on ADHD medications responded more symptomatically similar to their un-medicated selves when their medication status was not included on the questionnaire.…”
Section: Introductionmentioning
confidence: 99%